I AM, THEREFORE I'M NOT (WOMAN) - Sullivan, Moynagh (International Journal of English Studies, 2009)
This paper uses Object Relations theory to think about the dynarnics goveming the production of cultural identity in Irish Studies. Arguably wornen's writing is positioned within lrish studies in what Luce lrigaray terms "the place of the rnother". The rnother within the nuclear and patriarchal determined farnily is allocated the function of object through which the other rnernbers of the farnily derive their own identity. When a wornan writer inscribes her subjective presence then she disrupts the production of other's identity, and challenges the dynarnics of a farnily structure that need to rely on her absence frorn it. Such refusal to be sirnply an object is often rnet with resistance. This paper argues that Eavan Boland's collection The Lost Landalters Boland's object use within the cultural context of lrish studies, and it examines sorne of the criticisrn attaching to it accordingly.